ダイ 23 ジ ナンキョク チイキ カンソク タイ エットウ タイ ホウコク 1982-1983 - 星合, 孝男; ホシアイ, タカオ; Hoshiai, Takao (1984)
P(論文) 第23次日本南極地域観測隊越冬隊員34名は, 1982年2月1日から1年間, 昭和基地, みずほ基地を中心とした地域で各種観測を行った。極光, 地磁気, 電離層, 気象, 自然地震, 潮汐, 測地の定常諸観測を例年どおり実施した。「極域中層大気の総合観測」(MAPの一環), 「南極沿岸生態系における生物生産の基礎研究」(BIOMASSの一環), 「東クィーンモードランド地域雪氷・地学研究計画」(IAGPの一環)の3長期研究計画に基づく初年度の研究, および医学の研究を行い, 所期の目的をほぼ達成することができた。 The wintering party of the Japanese Antarctic Research Expedition (1982-1983) consisting of 34 members carried out multidisciplinary observations in the vicinity of Syowa Station and Mizuho Station between February 1982 and January 1983. The routine and fundamental observations comprising studies of aurora, geomagnetism, ionosphere, meteorology, oceanography, seismology and geodesy were performed as in the preceding years. Researches on the physical and chemical properties of the middle atmosphere and ecological investigations of marine coastal ecosystems were conducted in the Syowa Station area through the wintering season. To clarify dynamics of the ice sheet, glaciological studies were carried out in the Mizuho Plateau by the oversnow traverses, in particular the spring-summer traverse. Geological survey and meteorite search were also made in the Yamato Mountains area on the way of the spring-summer traverse. departmental bulletin paper